The Performance of Bamboo Truss with Gapit Form Under Vertical Loads - Amelia Shafa Kartika; Yulianto Purwono Prihatmaji (DIMENSI (Journal of Architecture and Built Environment), 2023)
The connection in bamboo construction is frequently the weakest point. This research discusses the performance of the gapit form on bamboo truss that effectively optimises the bamboo's inherent strength and can sustain vertical loads. Gapit is a connection form where a member is located between two members which also serves as a construction reinforcement. This truss optimizes the strength of whole bamboo with a total span of 4 meters and height of 2 meters. The gapit form applied at the top chord member, bracing member, and "V" support and column connections which are strengthen with bolts on the bamboo node. This research uses a quantitative method where data collection is taken through an experiment. To test the strength of the truss, a vertical hydraulic compression test was conducted. It was found that the truss can withstand a maximum load of up to 8.72 kN, with a truss decline of 7.27 cm, and a shift of 2 cm. As a result, the use of the gapit form on the truss is considered effective in withstanding large vertical loads.